Desenvolvimento de matriz biológica derivada de pele de tilápia do nilo (Oreochromis niloticus) e avaliação de sua biocompatibilidade em ratos - Martins, Camila Barroso (2023)
Regenerative medicine is a therapeutic technique that uses cells, tissues or organs to restore or replace normal body functions. Several conditions require the replacement and regeneration of organs and tissues, from clinical to pathological, such as traumatic injuries, diseases, genetic defects and aging. Tilapia Skin is considered a raw material for a new biomaterial, its similarity with human skin, its collagen content and its mechanical properties confirm the effectiveness of its use. In this study, the objective was to develop a decellularized tilapia skin dermal matrix (scaffold) and evaluate its histological structure, toxicity, inflammatory potential and subcutaneous absorption in rats. This is an in vitro and in vivo study with male heterogenic rats of the Wistar lineage (Rattus novergicus), developed to evaluate histological morphology, analysis of microbial load, evaluation of cytotoxicity (through MTT), quantification of DNA and analysis of types of collagen remaining from tilapia skin scaffolds. In vivo tests, the inflammatory profile of the biomaterial was evaluated through histological, hematological and biochemical analyses. In histological evaluation, the scaffolds presented structures with compacted collagen bundles, followed by sparse and fragmented bundles, and no cell nuclei were visualized. The biomaterials developed were considered non-toxic products, enabling cell viability greater than 95% after irradiation. The decellularization process was effective, as it eliminated more than 90% of DNA from the original tissue. There was no microbial load detected after the decontamination and irradiation process. The application of scaffolds irradiated at 25kGy did not cause intense inflammatory processes and there were no biochemical and hematological changes in the experimental groups. The results obtained indicate that Tilapia Skin scaffolds are effective and safe biomaterials for use in regenerative medicine.